Cross-Generational Leadership Communication Preferences in High-Context and Low-Context organizations within Energy Sector. - Bhattacharjee, Rashmi (Digital Repository of Theses, 2024)
In today's rapidly evolving organizational landscape, effective leadership communication is paramount for fostering collaboration, driving innovation, and achieving strategic objectives. However, navigating cross-generational differences in communication preferences presents a formidable challenge for leaders seeking to engage and motivate diverse teams. In the tapestry of contemporary organizational leadership, the intergenerational and cultural dimensions of communication stand out as pivotal threads. This thesis, titled "Cross-Generational Leadership Communication Preferences in High-Context and Low-Context Settings," ventures into the intricate domain of how emerging and established leaders navigate the spectrum of communication in varied cultural milieus. Drawing upon Edward T. Hall's (1976) dichotomy of high-context (HC) and lowcontext (LC) cultures, this study probes the alignment between generational communication proclivities and the inherent nuances of HC and LC environments (Hall, 1976). With a compact yet potent dataset derived from in-depth interviews with 60 leaders spanning three generational cohorts—Baby Boomers, Generation X, and Millennials—in a single industry, the research adopts a qualitative narrative analysis to unearth the subtleties of leadership communication. This methodological choice, inspired by the principles laid out by Braun and Clarke (2006), facilitates a deep dive into the personal narratives and experiences of the participants, offering a granular view of the interplay between generational identity and cultural context in leadership communication. The findings illuminate a fascinating evolution in leadership communication preferences, with a notable shift from the indirect, context-rich dialogues favored by Baby Boomers and Generation X, towards a more direct and explicit style preferred by Millennials. This generational pivot highlights a broader trend towards hybridization in communication styles, reflecting the pervasive influence of digital communication and cross-cultural exposure. The implications of this study resonate beyond the academic sphere, offering valuable insights for organizational leaders and human resource professionals. Echoing Northouse's (2018) emphasis on adaptability in leadership communication, this research underscores the necessity for leaders to tailor their communication strategies to the generational and cultural tapestry of their teams. As Bridges (2019) aptly notes, "Effective leadership is akin to a maestro conducting an orchestra of diverse instruments; each requires a unique touch to harmonize the ensemble." In sum, this thesis enriches the discourse on leadership communication by spotlighting the nuanced interrelations between generational cohorts and cultural contexts. It advocates for a paradigm shift towards more adaptable, context-aware leadership practices, capable of bridging the communicative divides across generations. Through this lens, the study contributes a valuable perspective to the ongoing dialogue on fostering inclusive, effective leadership in the multifaceted landscape of modern organizations.